Innovation in Islamic Philanthropy Development in Increasing the Inclusiveness of Cash Waqf in Indonesia - Fatkhur Rohman Albanjari; Fajriansyah Abdillah; Nugraheni Fitroh Rezqi Syakarna; Mazuri Binti Abd Ghani (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to explore innovations in Islamic philanthropy to enhance the inclusiveness of cash waqf in Indonesia. This research method employs a descriptive qualitative approach, utilizing data collection techniques that include interviews with five resource persons: the head of the institution, the cash waqf manager, the digital administrator, the waqf nadzir who collaborates with the foundation, and the waqif. Additionally, observation and documentation techniques were employed in this study. Data analysis was conducted using data reduction, field data presentation, and conclusion drawing. The results showed that, first, the importance of innovative and sustainable efforts in managing cash waqf. The innovation of access to cash waqf services in Yayasan Edukasi Wakaf Indonesia (YEWI) is demonstrated through various features and excellent programs, including collective, endowment, term, and tabarru' waqf, as well as Nazir Incubator Services, which enable communities to become part of the official waqf system. Second, the implementation of digitalizing cash waqf at YEWI has been carried out systematically and structurally through the Pasifamal.id platform, which encompasses the processes of collecting, managing, and distributing cash waqf. This digitalization makes transactions easier, faster, more transparent, and accountable. The platform offers a range of modern payment methods, including bank transfers, QRIS, and e-wallets, as well as real-time data on fund collection and comprehensive financial reports. This research gap demonstrates the importance of digital-based waqf, sustainable innovation, and collaboration in building an inclusive concept within Islamic philanthropy. These factors can build public trust and expand the reach of waqif to various levels of society.